Studies on sedimentation of asphaltene deposits in distillation residues - Lorek, Aneta; Paczuski, Maciej (Publishing House of Lviv Polytechnic National University, 2007)
Наведено експериментальні методи оцінки стабільності твердих речовин у дисперсіях рідин. Для характеристики дисперсійних компонентів застосовували сучасні аналітичні методи, такі, як тензіометрія, сканування і статична турбідиметрія. Показаний вплив відібраних поверхнево-активних речовин на стабільність дисперсій. Experimental methods used for the evaluation of stability of solids in liquids dispersions, are presented in this work. Modern analytical techniques, such as tensiometry, scanning and static turbidimetry, have been applied for the characterization of dispersion components. The influence of selected surface active substances on the dispersion stability has been demonstrated.
Дослідження седиментації асфальтенових відкладів у дистилятних залишках
Keywords: дисперсія; поверхневі властивості; стабільність; вакуумний залишок; dispersion; surface properties; stability; vacuum residue